On what is assessable in designs’ projects: Questions from a period of uncertainty (ARQUISUR Revista, 2014)
Reflexive document not derived from research. Some questions are proposed –starting from the analysis of assessment practices at Taller de Diseño I v at FADU-UNL– to reflect on what is assessable and teachable under the current crisis and reformulation of management [proyectualidad] and functionalism design paradigms. This proposal interrogates teachers’ modes of learning, the boundaries of the “raw material» offered by students which is in the beginning of teachers’ judgment criteria and also evaluation criteria.
Keywords: metacognition; design management; project; professional common sense